SOCIO-PEDAGOGICAL NECESSITY OF "SOFT SKILLS" IN THE OPTIMIZATION OF TEACHING FOREIGN LANGUAGES IN THE EDUCATIONAL SYSTEM (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2025)
Undoubtedly, one of the main goals of the higher education system is to prepare specialists who will effectively serve the labor market. The process of globalization, the development of production technologies, information and communication technologies, which is recognized as the fourth industrial revolution, made a great contribution to the emergence of new forms of work, the reshaping of working structures, the development of service and production sectors, and this, in turn, did not fail to have an impact on the labor market.